PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMANDIRIAN DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA KELAS V SEKOLAH DASAR - Sholikha, Mar'atus; Andriani Kumala Dewi, Ririn; Hadiansah, Dede (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the influence of the discovery learning model on students' independence and learning outcomes in science learning in the fifth grade of elementary school. The background of this research is the importance of learning independence and good learning outcomes in facing the challenges of 21st-century education. The discovery learning model is considered one approach that can improve students independence and learning outcomes. This study used a quantitative method with an empiricism positivism approach. Data were collected through tests and questionnaires given to fifth-grade students of SD NU Kaplongan. Data analysis was performed using descriptive and inferential statistics. The results showed that there was a significant influence between the discovery learning model on students' learning independence. This is evidenced by the significance value (Sig. (2-tailed)) 0.000 < α 0.05. In addition, there is a significant influence between the discovery learning model on student learning outcomes with a Sig value. (2-tailed) of 0.021 < α 0.05. Furthermore, learning independence also influences the improvement of student learning outcomes with a significance value of 0.009 < 0.05. Based on the results of this study, it can be concluded that the discovery learning model has a positive influence on students independence and learning outcomes in fifth-grade science learning. This model can be an effective alternative to improve the quality of science learning in elementary schools.